Mastectomy versus conservative surgical treatment: the impact on the quality of life of women with breast cancer Mastectomia versus tratamento cirúrgico conservador: impacto na qualidade de vida de mulheres com câncer mamário - Daniela Francescato Veiga; Fabíola Soares Moreira Campos; Leda Marques Ribeiro; Ivanildo Archangelo Junior; Joel Veiga Filho; Yara Juliano; Miguel Sabino Neto; Lydia Masako Ferreira (Instituto Materno Infantil de Pernambuco, 2010)
OBJECTIVES: to compare the impact of mastectomy and conservative surgery on the quality of life of patients with breast cancer. METHODS: an assessment was made of the quality of life of patients undergoing mastectomy or segmentary mastectomy, at the Pouso Alegre Clinical Hospital, in the Brazilian State of Minas Gerais, using SF-36. The patients were grouped by age (<50 years and >50 years) and years of schooling (<8 years and >8 years). The Mann-Whitney test was used to compare the groups with regard to the age and schooling domains of SF-36. RESULTS: a significant difference between the two groups was found in the domains of "physical functioning" (p=0.04) and "pain" (p=0.01): with the patients undergoing a mastectomy registering the worst scores. Young patients who had undergone a mastectomy displayed the worst quality of life in terms of "physical functioning" (p=0.03), "pain" (p=0.01) and "social functioning" (p=0.01); those undergoing conservative surgery aged over 50 years scored worst on "role emotional" (p=0.05). Patients undergoing a mastectomy with lower levels of schooling scored lower in "physical functioning" (p=0.01), "role physical" (p=0.05) and "pain" (p=0.05). Among those who had attended school for more than eight years, those having undergone a mastectomy scored less in the "pain" domain (p=0.04). CONCLUSIONS: patients who had undergone a mastectomy had worse results in the physical component of the evaluation of quality of life and this negative impact was more strongly felt among younger patients and those with lower levels of schooling. OBJETIVOS: comparar o impacto da mastectomia e da cirurgia conservadora na qualidade de vida de pacientes com câncer mamário. MÉTODOS: avaliou-se qualidade de vida de pacientes submetidas à mastectomia ou à mastectomia segmentar, no Hospital das Clínicas de Pouso Alegre, Minas Gerais, Brasil, utilizando-se o SF-36. As pacientes foram estratificadas quanto à idade (<50 anos e >50 anos) e escolaridade (<8 anos e >8 anos). Aplicou-se o teste de Mann-Whitney para comparar os grupos quanto aos domínios do SF-36, idade e escolaridade. RESULTADOS: observou-se diferença significante entre os grupos nos domínios "capacidade funcional" (p=0,04) e "dor" (p=0,01): as pacientes mastectomizadas com piores resultados. Pacientes mastectomizadas mais jovens apresentaram pior qualidade de vida em "capacidade funcional" (p=0,03), "dor" (p=0,01) e "aspectos sociais" (p=0,01); as submetidas à cirurgia conservadora, com mais de 50 anos, resultado pior em "aspectos emocionais" (p=0,05). Pacientes mastectomizadas com menor escolaridade apresentaram escores menores em "capacidade funcional" (p=0,01), "aspectos físicos" (p=0,05) e "dor" (p=0,05). Entre as que frequentaram a escola por mais de oito anos, as mastectomizadas pontuaram menos no domínio "dor" (p=0,04). CONCLUSÕES: pacientes mastectomizadas apresentaram piores resultados no componente físico da qualidade de vida, e este impacto negativo foi mais acentuado entre pacientes mais jovens e com menor escolaridade.